ANALISIS KEMAJUAN HARGA KEPADA PENINGKATAN BUNGA BANK INDONESIA TERHADAP KEKAYAAN BERSIH DAN DAMPAK INFLASI (STUDI KASUS PENDANAAN SYARIAH INDONESIA 2018-2020) - FUDLA AZZUHRA RAHMAWAN; PUSPA INDAH SARI POHAN; RAUDAH UCI MAYASARI MANIK3; KHAIRINA TAMBUNAN (JURNAL ILMIAH MAKSITEK, 2022)
Net worth is the focus of investors because it represents the total daily net value of investment funds. The purpose of this paper is to examine the impact of inflation and repo rates on the net assets of Bank Indonesia's long-term Islamic funds. Price increases indicate an increase in total cost of goods and occurs over a long period of time or continuously. At the right time, Bank Indonesia's repo rate is an internal rate set by the national bank and also distributed to the public. Methods of in-depth research are explanatory and numerical data, supported by a scan of the literature and numerical documentation and are data-driven. In this study, the results showed that inflation partially affected net assets by 61.1 percent, Bank Indonesia's repo rate did not affect total assets, while inflation and the BI 7-day repo rate affected net assets by 61.1 percent, 60 percent . three point one, Islamic/Sharia Fund.